2007
DOI: 10.1002/tt.34
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory fretting tests with thin wire specimens

Abstract: Wire ropes, due to their construction and application, are prone to fretting damages. In order to know the wear behaviour of individual wires under fretting conditions, laboratory tests are required. The present work describes the preliminary fretting tests accomplished with thin steel wires to optimise the testing procedure. The tests were carried out with 'crossed-cylinders' configuration varying the stroke and normal load. Afterwards, the fretted surfaces were characterised by means of an optical and scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Further characterization like shape, size of worn surface, crack size etc. can be done by using optical and scanning electron microscope, and a diamond stylus [59]. A steel wire consist of core filament, a first layer of intermediate steel filaments twisted around the core and a second layer of second steel filaments twisted around the first layer.…”
Section: Fretting Behavior Of Wire Ropementioning
confidence: 99%
“…Further characterization like shape, size of worn surface, crack size etc. can be done by using optical and scanning electron microscope, and a diamond stylus [59]. A steel wire consist of core filament, a first layer of intermediate steel filaments twisted around the core and a second layer of second steel filaments twisted around the first layer.…”
Section: Fretting Behavior Of Wire Ropementioning
confidence: 99%
“…The fretting wear leads to a higher wear, crack initiation and propagation of steel wires, and a considerable decrease in the fatigue lifetime of steel wire ropes. [1][2][3] On the other hand, steel wire rope in a coal mine remains in a harsh environment for a long period, such as high humidity, gale force wind, and acid-base erosion. As a large number of harmful ions in mine water trickling and coal bed bring corrosion on steel wire surfaces, the destructive effect of fretting corrosion is more serious than individual corrosion or fretting wear, which can accelerate the failure process of the steel wires.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have focused on dry friction in air in order to study the fretting wear and fretting fatigue of steel wires. Urchegui 2 analyzed fretting wear of thin steel wires using different operational variables such as normal force, stroke, and number of cycles. Also, Cruzado et al 4 mainly investigated the effect of contact pressure on fretting wear of thin steel wires and found that the wear coefficient increased with normal load and stroke, wear behavior was more aggressive in the running-in period, and the wear rates in the stable period increased with higher loads or strokes.…”
Section: Introductionmentioning
confidence: 99%